2018
DOI: 10.1155/2018/6942131
|View full text |Cite
|
Sign up to set email alerts
|

CT Perfusion in Patients with Lung Cancer: Squamous Cell Carcinoma and Adenocarcinoma Show a Different Blood Flow

Abstract: Objectives To characterize tumour baseline blood flow (BF) in two lung cancer subtypes, adenocarcinoma (AC) and squamous cell carcinoma (SCC), also investigating those “borderline” cases whose perfusion value is closer to the group mean of the other histotype. Materials and Methods 26 patients (age range 36-81 years) with primary Non-Small Cell Lung Cancer (NSCLC), subdivided into 19 AC and 7 SCC, were enrolled in this study and underwent a CT perfusion, at diagnosis. BF values were computed according to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
(58 reference statements)
2
15
1
Order By: Relevance
“… 14 , 15 Most literature, such as Bevilacqua A, etc, reported that the blood supply, enhanced scanning arteriovenous phase CT value, iodine content, and effective atomic number of adenocarcinoma was higher than squamous cell carcinoma. 16 However, in this study, no statistical difference was found in the arteriovenous CT value, iodine concentration, and effective atomic number between the adenocarcinoma and squamous cell carcinoma groups, which may be caused by the following reasons: Squamous cell carcinoma is often accompanied by irregular necrosis within the tumor. To avoid necrosis, the surrounding area of the tumor is selected for measurement.…”
Section: Discussioncontrasting
confidence: 62%
“… 14 , 15 Most literature, such as Bevilacqua A, etc, reported that the blood supply, enhanced scanning arteriovenous phase CT value, iodine content, and effective atomic number of adenocarcinoma was higher than squamous cell carcinoma. 16 However, in this study, no statistical difference was found in the arteriovenous CT value, iodine concentration, and effective atomic number between the adenocarcinoma and squamous cell carcinoma groups, which may be caused by the following reasons: Squamous cell carcinoma is often accompanied by irregular necrosis within the tumor. To avoid necrosis, the surrounding area of the tumor is selected for measurement.…”
Section: Discussioncontrasting
confidence: 62%
“…A previous study showed that BV and flow‐extraction product (i.e., K Trans in this study) are significantly higher in AC than in SCC . Another study also showed that before treatments, the AC histological type has a BF mean value significantly greater than SCC subtype . Even though the systemic arterial input DP model‐derived PS, vI and K Trans appeared statistically significant, the fitting error of the systemic arterial input DP model was considerably larger than that of the dual‐input 2CX model in NSCLC (Table ).…”
Section: Discussionmentioning
confidence: 43%
“…However, on analysing the values, we noted that two lesions (ID14 and ID40) had very low perfusion values (BF <20 mL/100 g/min), causing skewness of the data and negatively affecting the study’s statistical significance [ Figure 3 ]. Inspired by Bevilacqua et al ,[ 13 ] we excluded these two cases, which revealed statistically significant differences in BF (f = 5.563, P = 0.007), BV (f = 3.548, P = 0.038) and FE (f = 3.617, P = 0.036) in different lung carcinoma subtypes (N = 44) [ Table 3 ]. MTT did not show any statistically significant differences between the subtypes.…”
Section: Resultsmentioning
confidence: 99%